Recent Advances in Enhancing Air Stability of Layered Oxide Cathodes for Sodium-Ion Batteries via High-Entropy Strategies - Zhenyu Cheng; Tao Du; Lei Cao; Yuxuan Liu; Hao Wang (Metals)
Layered transition metal oxide (LTMO) cathode materials for sodium-ion batteries (SIBs) have attracted extensive attention due to their unique structural stability and excellent electrochemical performance. However, their poor stability in air has significantly impeded their practical application, as exposure to moisture and carbon dioxide can lead to Na+ loss, phase transitions, and decreased electrochemical performance. This paper reviews the application of high-entropy strategies in sodium-ion LTMO cathode materials, focusing on the optimization of air stability and electrochemical performance through approaches including high-entropy cation regulation, P2/O3 dual-phase synergistic structures, and fluorine ion doping. Studies have shown that high-entropy design can effectively inhibit phase transitions, alleviate Jahn–Teller distortion, enhance oxygen framework stability, and markedly enhance the cycle life and rate performance of materials. Furthermore, future research directions are proposed, including the use of advanced characterization techniques to reveal failure mechanisms, the integration of machine learning to optimize material design, and the development of high-performance mixed-phase structures. High-entropy strategies provide new perspectives for the development of SIBs cathode materials with enhanced air stability, potentially promoting the practical application of SIBs in large-scale energy storage systems.